"People Who Do Not Understand Irony Cannot Understand Fiction": An Interview with Tabish Khair. (2nd January 2021) - Ramzan, Muddasir
Abstract: In this detailed interview with Muddasir Ramzan, Tabish Khair discusses his role as a writer, with a special focus on his novel Just Another Jihadi Jane (Northampton, MA: Interlink Books, 2016). He expresses his views on Muslim identity, his life as a writer and academic in Denmark, Islamophobia and Muslims in the West, re-orientalism and the politics of representation, comprador intellectuals, his response to the Rushdie Affair, and post-9/11 discourses. This interview also elicits his thoughts on shifting between different genres of writing, censorship, European colonisation, many categories of Muslims, religious fundamentalisms, surveillance, the internet and social media, "jihadi janes", extremism, ISIS returnees and the burning of books, and other postcolonial themes.